Pengaruh Transformasional Leadership, dan Psycologi Capital Terhadap Work Engagement Pada Karyawan Perusahaan di Kota Salatiga - Darwati, Darwati (Peneliti.net, 2024)
World economic growth experienced a downward correction. High inflation and declining economic growth are predicted to experience a global recession in 2023. It threatens companies to go bankrupt, and companies are forced to streamline operational costs with the psychology and performance of employees. In addition, Indonesia is entering the 5.0 revolution era and a transitional period from the co-19 pandemic. The troubles on the way to be tested are the impact of transformational leadership and the psychology of capital on work engagement among Company employees in Salatiga City. The purpose of this study was to study the effect of transformational leadership and the psychology of capital on work engagement among company employees in Salatiga City. The benefit of this research is to expedite the company's operational activities in dealing with an economic recession, adjusting the transitional environment after the Covid-19 pandemic. This scientific study was conducted on the workforce working in the City of Salatiga based on the Central Bureau of Statistics for the City of Salatiga, totaling 103,979 people. The sampling method uses a probabilistic sampling method, which equates the probability that each element (member) of the population will be selected as a member of the sample. Sampling using simple random sampling, namely taking members of the sample and population is done randomly without paying attention to the layers in the population. Sampling was carried out in the study using calculations with the Slovin formula with a total sample of 100 employees. The data analysis technique to answer the research hypothesis uses the Smart Partial Least Square (PLS) tool. The output of this research is a Sinta 5 accredited journal or National Seminar Call for Paper.